Method for producing degradable material from dendrocalamus latiflorus leftovers
By preparing the scraps of mahjong bamboo shoots into nanocellulose-polylactic acid degradable materials, the problems of waste of scraps and environmental pollution are solved, efficient resource utilization and low-cost production are achieved, and high-value-added products with good mechanical properties and biodegradability are provided.
Patent Information
- Application Number
- CN202411891335.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The large amount of scraps produced during the processing of bamboo shoots cannot be effectively utilized, resulting in waste of resources and environmental pollution.
Nanocellulose-polylactic acid degradable material is prepared by preparing the scraps of bamboo shoots and using acid hydrolysis method to make nanocellulose, and finally blended with polylactic acid to prepare nanocellulose-polylactic acid degradable material.
It has achieved efficient resource utilization of scraps under bamboo shoots, reduced environmental pollution, simple production process and low cost, suitable for large-scale production, and provided high-value-added products with good mechanical properties and biodegradability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable materials, and in particular to a method for producing degradable materials from leftover bamboo shoots. Background Art
[0002] Bamboo shoots (Dendrocalamus latiflorus), also known as sweet bamboo, big green bamboo, and wadoni bamboo, are a plant of the Poaceae family. They are known as "Lingnan mountain treasures" and are praised as "the first green health food". In recent years, with the rapid development of the bamboo shoot industry, the output of bamboo shoot related products such as dried bamboo shoots and canned bamboo shoots has increased.
[0003] However, the bamboo shoots used to make canned bamboo shoots, dried bamboo shoots and other bamboo shoot products only account for 30% of the bamboo shoots, while the remaining 70% are scraps such as bamboo shoot heads and shells. These parts are rich in useful components such as cellulose and lignin. Directly discarding them will lead to a waste of resources and may pollute the soil, water and air after being discarded, threatening the ecological environment. Therefore, resource processing of the scraps of Bamboo shoots and the development of high value-added products are of great significance to promoting the circular economy in the agricultural and industrial fields, reducing dependence on natural resources, reducing the production and social management costs caused by the removal and landfill of a large amount of scraps, and realizing the efficient use of resources. Summary of the invention
[0004] In view of this, the present invention provides a method for producing degradable materials from bamboo shoots waste, and the method uses bamboo shoots waste as raw materials to prepare nanocellulose-polylactic acid degradable materials. The preparation of degradable materials from bamboo shoots waste of the present invention reduces environmental pollution, improves resource utilization, and has a simple process, low cost, and is suitable for large-scale production. The obtained degradable material has good mechanical properties and biodegradability, is suitable for biomedicine, packaging materials and agricultural fields, and provides a new direction for the resource application of bamboo shoots waste.
[0005] The present invention provides a method for producing a degradable material from bamboo shoots waste, comprising the following steps:
[0006] Firstly, microcrystalline cellulose is prepared by using bamboo shoot waste as raw material, then the prepared microcrystalline cellulose is prepared into nanocellulose by acid hydrolysis method, and finally the nanocellulose and polylactic acid are used to prepare nanocellulose-polylactic acid degradable material.
[0007] Preferably, the bamboo shoots scraps are at least one of bamboo shoot skins, bamboo shoot stumps, and bamboo shoot shells.
[0008] The method for preparing microcrystalline cellulose using bamboo shoots waste as raw materials comprises the following steps:
[0009] The bamboo shoot waste is pretreated and then boiled with alkali, bleached, acid-lyzed, washed and filtered to obtain microcrystalline cellulose.
[0010] Preferably, the pretreatment method is as follows: the leftover bamboo shoots are dried and then crushed, and the crushed leftover bamboo shoots are soaked in a citric acid-acetic acid mixture at room temperature, and after the soaking is completed, the leftover bamboo shoots are filtered, washed, and dried to complete the pretreatment of the leftover bamboo shoots.
[0011] The preparation method of the cellulose-polylactic acid composite degradable material is as follows:
[0012] The prepared microcrystalline cellulose is prepared into nanocellulose by acid hydrolysis, the nanocellulose and polylactic acid are dried and evenly mixed to obtain a mixture, the mixture is melt-blended and then extruded and granulated to obtain a nanocellulose-polylactic acid degradable material.
[0013] Preferably, the amount of the nanocellulose is 8 wt.% to 12 wt.% of the polylactic acid.
[0014] The present invention also provides an application of a cellulose-polylactic acid composite degradable material in the fields of biomedicine, packaging materials, agriculture, etc. The cellulose-polylactic acid composite degradable material is the cellulose-polylactic acid composite degradable material described in the above technical solution.
[0015] The present invention uses a large amount of waste (bamboo shoots, bamboo shoots, bamboo shoot shells) generated during the processing of bamboo shoots as raw materials, turning waste into treasure, reducing the difficulty of waste treatment and environmental burden, improving resource utilization efficiency, realizing the full life cycle cycle of industrial waste to degradable materials, and providing an economical and efficient solution to solve industrial waste pollution. The present invention uses a citric acid-acetic acid mixed solution combined with ultrasonic immersion for pretreatment, which has the characteristics of mildness and high efficiency and can improve the mechanical properties of degradable materials. The present invention enhances the strength and toughness of polylactic acid by compounding nanocellulose with polylactic acid, and solves the problem of its easy brittle cracking. The present invention uses melt blending technology to uniformly distribute nanocellulose in polylactic acid, thereby significantly improving the comprehensive performance of the composite material. The composite material of the present invention maintains good biodegradability, can be quickly decomposed in the natural environment, and reduces plastic pollution. The entire preparation process of the present invention has a reasonable process design, clear steps, easy-to-control parameters, and is suitable for large-scale production. Bamboo shoot scraps are low-cost waste with abundant sources. Compared with the use of pure cellulose or chemical raw materials to prepare microcrystalline cellulose and composite materials, the material cost is significantly reduced. The obtained microcrystalline cellulose and nanocellulose-polylactic acid composite materials are both high value-added products, which are widely used in food packaging, biomedicine, agricultural films and other fields, opening up a new economic growth point for the bamboo shoot processing industry chain. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The present invention provides a method for producing a degradable material from bamboo shoots waste, comprising the following steps:
[0018] Firstly, microcrystalline cellulose is prepared by using bamboo shoot waste as raw material, then the prepared microcrystalline cellulose is prepared into nanocellulose by acid hydrolysis method, and finally the nanocellulose and polylactic acid are used to prepare nanocellulose-polylactic acid degradable material.
[0019] In a specific implementation manner of the present invention, the bamboo shoots waste materials are preferably at least one of bamboo shoot skins, bamboo shoot stumps, and bamboo shoot shells.
[0020] Bamboo shoot skin refers to the outer skin of bamboo shoots, which is a thin layer of skin that is gradually formed during the growth of bamboo shoots. This layer of skin is usually peeled off when processing bamboo shoots, and it is a common by-product of bamboo shoot processing. Bamboo shoot skin is rich in cellulose and hemicellulose, contains a certain amount of lignin, and has good water absorption and air permeability. Bamboo shoot stump refers to the root of bamboo shoots, which plays a role of fixation and support during the growth of bamboo shoots. It is usually cut off when processing bamboo shoots, and it is a common by-product of bamboo shoot processing. Bamboo shoot stump is rich in cellulose and hemicellulose, contains a high content of lignin, and has a certain hardness and toughness. Bamboo shoot shell refers to the hard shell part inside the bamboo shoot, which is usually removed during the processing of bamboo shoots, and it is a common by-product of bamboo shoot processing. Bamboo shoot shell is rich in cellulose and hemicellulose, contains a high content of lignin, and has a certain hardness and toughness.
[0021] In the process of processing bamboo shoots, a large amount of waste such as bamboo shoot skins, bamboo shoot stumps, and bamboo shoot shells will be generated, which are collectively referred to as bamboo shoot scraps. Therefore, the effective use of bamboo shoot skins, bamboo shoot stumps, and bamboo shoot shells is of great significance to reducing the pollution of agricultural waste to the environment, creating economic value, and promoting sustainable development.
[0022] Microcrystalline cellulose is a hydrolysis product of natural plant cellulose hydrolyzed to the limiting degree of polymerization (LODP) by dilute acid. It is a highly purified, partially crystallized form of cellulose with extremely strong fluidity and is in the form of extremely fine short rods or powdered porous particles. Microcrystalline cellulose has properties such as a low degree of polymerization and a large specific surface area, and has strong reactivity in a variety of chemical reactions. The present invention takes into account the characteristics of the leftovers of bamboo shoots, selects it as a raw material for the preparation of high-quality microcrystalline cellulose, and uses it as a raw material to prepare a degradable material. This method is a method for effectively utilizing the leftovers of bamboo shoots, which not only reduces environmental pollution, but also creates higher economic value.
[0023] The first step of the present invention is to pretreat the leftovers of the bamboo shoots. The specific method is as follows: the leftovers of the bamboo shoots are dried at 45°C to 65°C to a water content of ≤12wt.%, and then crushed to a particle size of 20 to 40 meshes, and soaked in a citric acid-acetic acid mixed solution at room temperature for 60 to 120 minutes according to a solid-liquid ratio of 1g: (10 to 20) mL, filtered, washed, and dried at 45°C to a water content of ≤15wt.% to complete the pretreatment of the leftovers of the bamboo shoots. The citric acid-acetic acid mixed solution is prepared by uniformly mixing citric acid, acetic acid and water, and the concentrations of citric acid and acetic acid in the citric acid-acetic acid mixed solution are both 2wt.% to 5wt.%.
[0024] In some preferred embodiments of the present invention, the immersion is ultrasonic immersion, the ultrasonic power is 300-400W, and the immersion time is 10-30min.
[0025] Bamboo shoots scraps contain cellulose, hemicellulose, lignin and other impurities (such as fat, protein, etc.). Citric acid-acetic acid mixed solution has certain acidity, can dissolve some impurities (such as fatty acids, soluble lignin, etc.), while maintaining the stability of cellulose structure, thereby improving cellulose purity. The acidic conditions provided by organic acid can destroy the combination between some hemicellulose and lignin, making cellulose easier to subsequent chemical treatment (such as alkali boiling and acid hydrolysis), improving the extraction efficiency of microcrystalline cellulose. In addition, the present invention's research shows that, compared with not pre-treatment, after pre-treatment of raw materials with citric acid-acetic acid mixed solution, subsequent product production efficiency has been greatly improved, and the extraction rate and quality of cellulose also have a more obvious improvement, which is finally reflected in the improvement of tensile strength and toughness of degradable materials.
[0026] In addition, the use of citric acid-acetic acid mixed solution as the pretreatment solution is the result of optimized selection. Compared with other organic acids, organic acid-inorganic acid, and inorganic acid combinations, the necessity of citric acid-acetic acid mixed solution in the present invention is reflected in the following aspects:
[0027] First, both citric acid and acetic acid are weak organic acids that will not significantly damage the main chain structure of cellulose, which ensures the integrity and purity of cellulose. Secondly, citric acid and acetic acid show a synergistic effect in dissolving lignin, hemicellulose and other impurities, among which citric acid has a strong complexing ability and acetic acid has good organic solubility. In addition, citric acid and acetic acid are both organic acids of natural origin, with low toxicity and biodegradability, and have a small burden on the environment when treating waste liquid. At the same time, citric acid and acetic acid can effectively destroy the lignin and hemicellulose binding layer on the surface of cellulose, but will not cause excessive crystallization or degradation of the cellulose structure, and the combination can achieve good pretreatment effects under relatively mild conditions (45°C to 65°C) and at lower concentrations. Finally, citric acid and acetic acid are both common chemicals with low prices and stable supply, and have cost advantages in industrial-scale production.
[0028] During the research and development process of the present invention, other combinations were also tried, for example: oxalic acid-formic acid, however, this combination is highly acidic and may cause excessive degradation or structural damage of cellulose, and cannot be used for protective pretreatment; propionic acid-butyric acid has low organic solubility and limited effect on the removal of lignin or lipids; succinic acid-lactic acid has a high cost and is difficult to promote industrially.
[0029] Therefore, after comprehensively considering factors such as chemical properties, environmental protection, treatment effect and economy, the selection of citric acid-acetic acid mixed solution is necessary and the best choice for the present invention, which achieves a balance between effectiveness, cost control and environmental friendliness and has irreplaceable advantages.
[0030] The second step of the present invention is to use the pre-treated bamboo shoots as raw materials to prepare microcrystalline cellulose, and the specific method is as follows:
[0031] The pretreated bamboo shoots and scraps are mixed with NaOH accounting for 20-35% of the total mass of the bamboo shoots and scraps, and then steamed at 80-100°C for 30-45 minutes, washed with water until neutral and filtered, the steamed product is mixed with H2O2 for bleaching, and then the steamed product is mixed with hydrochloric acid with a concentration of 2wt.%-8wt.% at a ratio of 1g:(10-20)mL, and acid-hydrolyzed at 70-85°C for 20-30 minutes. After the cellulose reaches a balanced degree of polymerization, it is washed with water until neutral, filtered, and microcrystalline cellulose is obtained.
[0032] In some specific embodiments of the present invention, the bleaching treatment temperature is 35° C. to 55° C., and the treatment time is 20 to 60 minutes. The present invention does not strictly limit the amount and concentration of H2O2, and it can be based on actual needs to balance economic benefits and treatment effects.
[0033] The third step of the present invention is to prepare a degradable material with the prepared microcrystalline cellulose as a raw material. The specific method is as follows: the prepared microcrystalline cellulose is mixed with water to prepare a 10wt% microcrystalline cellulose solution, and then concentrated sulfuric acid is added dropwise under stirring at 60°C, reacted for 30 minutes, centrifuged to remove the supernatant, and repeated 2-3 times, and the pH value is adjusted to neutral to obtain nanocellulose, and the prepared nanocellulose and polylactic acid are dried and mixed uniformly to obtain a mixture, and the mixture is melt-blended at 30-60r / min, and then extruded and granulated at 170-190°C to obtain a nanocellulose-polylactic acid degradable material.
[0034] In a specific embodiment of the present invention, the amount of the nanocellulose is 8wt.% to 12wt.% of the polylactic acid.
[0035] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available.
[0036] Unless otherwise specified, all experiments were repeated three times. SPSS 21.0 was used for analysis of variance (ANOVA) and Duncan's multiple comparison analysis. The results were expressed as mean ± standard deviation, and P < 0.05 indicated a significant difference.
[0037] Embodiment 1 A method for producing a degradable material from bamboo shoots waste, comprising the following steps:
[0038] S1, the bamboo shoots scraps (the mass ratio of bamboo shoot skin, bamboo shoot stump and bamboo shoot shell is 1:1:3) are dried at 65°C to an average water content of 8.2wt.%, crushed and passed through a 40-mesh sieve, and soaked in a citric acid-acetic acid mixed solution at room temperature for 90min according to a solid-liquid ratio of 1g:15mL, filtered, washed, and dried at 65°C to an average water content of 10.5wt.% to complete the pretreatment of the bamboo shoots scraps, the citric acid-acetic acid mixed solution is prepared by mixing citric acid, acetic acid and water, and the concentration of citric acid in the citric acid-acetic acid mixed solution is 3.5wt.%, and the concentration of acetic acid is 2.5wt.%;
[0039] S2, the pre-treated bamboo shoots and the waste materials and NaOH accounting for 25% of the total mass of the bamboo shoots and the waste materials are mixed and boiled at 100°C for 30min, washed with water until neutral and filtered, the boiled product is mixed with H2O2 with a concentration of 5wt.% at a solid-liquid ratio of 1g:10mL, the pH value is adjusted to 12, bleached at 35°C for 25min, and then the boiled product is mixed with hydrochloric acid with a concentration of 6wt.% at a solid-liquid ratio of 1g:15mL, acid hydrolyzed at 75°C for 30min to achieve equilibrium polymerization degree of cellulose, washed with water until neutral, filtered, and microcrystalline cellulose is obtained;
[0040] S3. The microcrystalline cellulose prepared in S2 is made into a 10 wt% microcrystalline cellulose aqueous solution, and then concentrated sulfuric acid is added dropwise at 60°C with stirring. After reacting for 30 minutes, the supernatant is removed by centrifugation, and the reaction is repeated 3 times. The pH value is adjusted to neutral to obtain nanocellulose. The prepared nanocellulose and polylactic acid are dried and evenly mixed, wherein the amount of the nanocellulose is 12 wt.% of the polylactic acid, to obtain a mixture. The mixture is melt-blended at 40 r / min, and then extruded and granulated at 175°C to obtain a nanocellulose-polylactic acid degradable material.
[0041] Embodiment 2 A method for producing a degradable material from bamboo shoots waste, comprising the following steps:
[0042] S1, the bamboo shoots scraps (the mass ratio of bamboo shoot skin, bamboo shoot stump and bamboo shoot shell is 1:3:1) are dried at 45°C to an average water content of 7.9wt.%, crushed and passed through a 40-mesh sieve, and soaked in a citric acid-acetic acid mixed solution at room temperature for 120min according to a solid-liquid ratio of 1g:10mL, filtered, washed, and dried at 55°C to an average water content of 9.9wt.% to complete the pretreatment of the bamboo shoots scraps, the citric acid-acetic acid mixed solution is prepared by mixing citric acid, acetic acid and water, and the concentration of citric acid in the citric acid-acetic acid mixed solution is 3.0wt.%, and the concentration of acetic acid is 3.0wt.%;
[0043] S2, the pre-treated bamboo shoots and the NaOH accounting for 35% of the total mass of the bamboo shoots were mixed and boiled at 80°C for 30min, washed with water until neutral and filtered, the boiled product was mixed with H2O2 with a concentration of 4.5wt.% at a solid-liquid ratio of 1g:12mL, the pH value was adjusted to 12, bleached at 55°C for 20min, and then the boiled product was mixed with hydrochloric acid with a concentration of 8wt.% at a solid-liquid ratio of 1g:12mL, acid hydrolyzed at 80°C for 22min to achieve equilibrium polymerization degree of cellulose, washed with water until neutral, filtered, and obtained microcrystalline cellulose;
[0044] S3, the microcrystalline cellulose prepared in S2 is made into a 10wt% microcrystalline cellulose aqueous solution, and then concentrated sulfuric acid is added dropwise at 60°C with stirring, reacting for 30 minutes and then centrifuging to remove the supernatant, repeating 3 times, adjusting the pH value to neutral to obtain nanocellulose, and drying the prepared nanocellulose and polylactic acid and mixing them evenly, wherein the amount of the nanocellulose is 10wt.% of the polylactic acid, to obtain a mixture, and the mixture is melt-blended at 45r / min, and then extruded and granulated at 180°C to obtain a nanocellulose-polylactic acid degradable material.
[0045] Embodiment 3 A method for producing a degradable material from bamboo shoots waste, comprising the following steps:
[0046] S1, the bamboo shoots scraps (the mass ratio of bamboo shoot skin, bamboo shoot stump and bamboo shoot shell is 2:1:2) are dried at 55°C to an average water content of 11.3wt.%, crushed and passed through a 40-mesh sieve, and ultrasonically soaked for 15min at 350W with a citric acid-acetic acid mixed solution at a solid-liquid ratio of 1g:13mL, filtered, washed, and dried at 60°C to an average water content of 13.7wt.% to complete the pretreatment of the bamboo shoots scraps, the citric acid-acetic acid mixed solution is prepared by mixing citric acid, acetic acid and water, and the concentration of citric acid in the citric acid-acetic acid mixed solution is 5.0wt.%, and the concentration of acetic acid is 2.0wt.%;
[0047] S2, the pre-treated bamboo shoots and the NaOH accounting for 20% of the total mass of the bamboo shoots were mixed and boiled at 100 ° C for 45 minutes, washed with water until neutral and filtered, the boiled product was mixed with H2O2 with a concentration of 4.5wt.% at a solid-liquid ratio of 1g:13mL, the pH value was adjusted to 12, bleached at 50 ° C for 28min, and then the boiled product was mixed with hydrochloric acid with a concentration of 7.5wt.% at a solid-liquid ratio of 1g:10mL, acid hydrolyzed at 85 ° C for 23min to reach the equilibrium polymerization degree of cellulose, washed with water until neutral, filtered, and obtained microcrystalline cellulose;
[0048] S3, the microcrystalline cellulose prepared in S2 is made into a 10wt% microcrystalline cellulose aqueous solution, and then concentrated sulfuric acid is added dropwise at 60°C with stirring, reacting for 30 minutes and then centrifuging to remove the supernatant, repeating 3 times, adjusting the pH value to neutral to obtain nanocellulose, and drying the prepared nanocellulose and polylactic acid and mixing them evenly, wherein the amount of the nanocellulose is 8wt.% of the polylactic acid, to obtain a mixture, and the mixture is melt-blended at 60r / min, and then extruded and granulated at 175°C to obtain a nanocellulose-polylactic acid degradable material.
[0049] Comparative Example 1
[0050] Same as Example 2, except that the citric acid-acetic acid mixture is replaced by an equal amount of 3.0 wt.% citric acid solution.
[0051] Comparative Example 2
[0052] Same as Example 2, except that the citric acid-acetic acid mixed solution is replaced by an equal amount of 3.0 wt.% acetic acid solution.
[0053] Comparative Example 3
[0054] Same as Example 2, except that the citric acid-acetic acid mixture is replaced by a citric acid-formic acid mixture, wherein the concentration of citric acid is 3.0 wt.%, and the concentration of formic acid is 3.0 wt.%.
[0055] Comparative Example 4
[0056] Same as Example 2, except that the citric acid-acetic acid mixture is replaced by an oxalic acid-formic acid mixture, wherein the concentration of oxalic acid is 3.0 wt.%, and the concentration of formic acid is 3.0 wt.%.
[0057] Comparative Example 5
[0058] Same as Example 2, except that the concentration of citric acid in the citric acid-acetic acid mixture is 8.0 wt.%, and the concentration of acetic acid is 8.0 wt.%.
[0059] Comparative Example 6
[0060] Same as Example 2, except that the concentration of citric acid in the citric acid-acetic acid mixture is 1.0 wt.%, and the concentration of acetic acid is 1.0 wt.%.
[0061] Comparative Example 7
[0062] Same as Example 2, except that the amount of nanocellulose used is 5 wt.% of the polylactic acid.
[0063] Comparative Example 8
[0064] Same as Example 2, except that the amount of nanocellulose is 15wt.% of polylactic acid.
[0065] The mechanical properties of the materials obtained in Examples 1-3 and Comparative Examples 1-8 were tested, and the test results are shown in Table 1.
[0066] The tensile properties are tested according to GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3: Test conditions for thin plastics and sheets”. The material is made into 1B type specimens of the same specifications by hot pressing, and each group of specimens consists of 10.
[0067] The impact performance is tested according to GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics". The material is made into specimens of the same specifications by hot pressing. The notch type is Type A, and each group of specimens consists of 10.
[0068] Table 1 Mechanical properties test results
[0069] Tensile strength (s / MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 29.61±0.65a 2.993±0.121a Example 2 28.55±0.53b 2.864±0.213ab Example 3 27.84±0.36bc 2.808±0.192ab Comparative Example 1 26.55±0.65de 2.520±0.115c Comparative Example 2 25.40±0.31f 2.692±0.126c Comparative Example 3 25.98±0.41ef 2.634±0.212c Comparative Example 4 25.63±0.26f 2.606±0.148c Comparative Example 5 25.69±0.64ef 2.634±0.137c Comparative Example 6 27.12±0.49cd 2.720±0.231a Comparative Example 7 18.84±0.51h 2.033±0.274c Comparative Example 8 21.12±0.58g 2.291±0.190c
[0070] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for producing degradable materials from bamboo shoots waste, characterized in that: The following steps are involved: Firstly, microcrystalline cellulose is prepared by using bamboo shoot waste as raw material, then the prepared microcrystalline cellulose is prepared into nanocellulose by acid hydrolysis method, and finally the nanocellulose and polylactic acid are used to prepare nanocellulose-polylactic acid degradable material.
2. The method for producing degradable materials from bamboo shoots waste according to claim 1, characterized in that: The bamboo shoot scraps are at least one of bamboo shoot skins, bamboo shoot stumps and bamboo shoot shells.
3. The method for producing degradable materials from bamboo shoots waste according to claim 1, characterized in that: The method for preparing microcrystalline cellulose using bamboo shoots waste as raw materials comprises the following steps: The bamboo shoot waste is pretreated and then boiled with alkali, bleached, acid-lyzed, washed and filtered to obtain microcrystalline cellulose.
4. The method for producing degradable materials from bamboo shoots waste according to claim 3, characterized in that: The pretreatment method is as follows: drying the leftover bamboo shoots and then crushing them, soaking the crushed leftover bamboo shoots in a citric acid-acetic acid mixture, filtering, washing, and drying after soaking, and completing the pretreatment of the leftover bamboo shoots.
5. The method for producing degradable materials from bamboo shoots waste according to claim 4, characterized in that: The citric acid-acetic acid mixed solution is prepared by uniformly mixing citric acid, acetic acid and water. The concentrations of citric acid and acetic acid in the citric acid-acetic acid mixed solution are both 2 wt.% to 5 wt.%.
6. The method for producing degradable materials from bamboo shoots waste according to claim 4, characterized in that: The material-liquid ratio of the dried bamboo shoots to the citric acid-acetic acid mixed solution is 1g:(10-20)mL.
7. The method for producing degradable materials from bamboo shoots waste according to claim 1, characterized in that: The preparation method of the cellulose-polylactic acid composite degradable material is as follows: The prepared microcrystalline cellulose is prepared into nanocellulose by acid hydrolysis, the nanocellulose and polylactic acid are dried and evenly mixed to obtain a mixture, the mixture is melt-blended and then extruded and granulated to obtain a nanocellulose-polylactic acid degradable material.
8. The method for producing degradable materials from bamboo shoots waste according to claim 7, characterized in that: The amount of the nanocellulose used is 8wt.% to 12wt.% of the polylactic acid.
9. A cellulose-polylactic acid composite biodegradable material, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. The present invention also provides an application of a cellulose-polylactic acid composite degradable material in the biomedical field, packaging material, and agricultural field, characterized in that: The cellulose-polylactic acid composite degradable material is a cellulose-polylactic acid composite degradable material prepared by the method according to any one of claims 1 to 8 or a cellulose-polylactic acid composite degradable material according to claim 9.